A strain based criterion to assess ductile failure initiation in dented pipelines under tensile loading. (August 2021) - Plata Uribe, Yerlin Andres; Ruggieri, Claudio; Ohata, Mitsuru
This work addresses the problem of describing ductile fracture behavior and predicting ductile failure initiation in dented pipelines under tensile loading based upon a 3-D computational cell approach coupled with a stress-modified, critical strain (SMCS) criterion for void coalescence. A series of tension tests conducted on notched tensile specimens with different notch radius for a carbon steel pipe provides the stress–strain response of the tested structural steel from which the SMCS criterion is calibrated. Full scale cyclic bend tests also performed on a 165 mm O.D tubular specimen with 11 mm wall thickness enable verification of the proposed approach in assessing ductile cracking behavior in damaged pipelines. These exploratory analyses predict the tensile failure load for the pipe specimen associated with ductile crack initiation in the highly damaged area inside the denting and buckling zone which are in good agreement with experimental measurements.